2000
DOI: 10.1006/jfin.1999.0278
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Lending within a Bank-Based System: Evidence from European Small Business Data

Abstract: This paper adds to the relationship lending debate by investigating detailed contract information obtained from examining nearly eighteen thousand bank loans. The beneficiaries all were very small firms that operate within the continental European bankbased system. That is, with data gathered for Belgium, we investigate price and non-price terms of the loan contract. We test for the possibility of intertemporal rent shifting by banks. The empirical evidence shows two opposing effects. On the one hand, the leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
482
4
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 757 publications
(534 citation statements)
references
References 32 publications
40
482
4
8
Order By: Relevance
“…Furthermore, because the accumulation of information is not linear over time and the benefits increase in a way which is less than proportional to time , it is not possible to exclude the possibility, in long-term relationships, that the borrower may be tempted to abandon them (Ongena and Smith, 2000). This also seems to be confirmed by Degryse and Van Cayseele (2000) who shows deterioration in contractual conditions applied to the debt as the duration of the relationship increases.…”
Section: Literature Reviewsupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, because the accumulation of information is not linear over time and the benefits increase in a way which is less than proportional to time , it is not possible to exclude the possibility, in long-term relationships, that the borrower may be tempted to abandon them (Ongena and Smith, 2000). This also seems to be confirmed by Degryse and Van Cayseele (2000) who shows deterioration in contractual conditions applied to the debt as the duration of the relationship increases.…”
Section: Literature Reviewsupporting
confidence: 59%
“…Similarly, Chakraborty and Hu (2006) find that the incidence of collateral pledge decreases with the number of lender-provided financial services used by the borrower. By contrast, other studies (Machauer and Weber 1998, Degryse and Van Cayseele 2000, Elsas and Krahnen 2002, Lehmann and Neuberger 2001, and Menkhoff et al 2006, Ono and Uesugi 2009) find that collateral is contract-term prevalent into the relationship between the borrowers and their main bank. However, understanding the role of collateral during a financial crisis implies to take into consideration other motivation that induce the banker to prefer secured loans.…”
Section: Literature Reviewmentioning
confidence: 85%
“…1, 2 2.1 The cost and availability of credit and multiple banking relationships: Theoretical considerations From a theoretical point of view, multiple relationship banking can have both advantages and disadvantages, both of which are related to the fact that relationship 1 A survey of more general issues regarding relationship banking is provided by Boot (2000). 2 This paper restricts itself to a discussion of multiple banking relationships, however the strength of banking relationships are measured in various ways: the duration of a bank-firm relationship (Petersen andRajan 1994, 1995;Cole 1998;Degryse and Van Cayseele 2000) and the number of different services the firm purchases from the bank (Degryse and Van Cayseele 2000). banks acquire private information on the borrowing firm.…”
Section: The Effect Of Multiple Banking Relationships On Credit Cost mentioning
confidence: 99%
“…The survey targets manufacturing firms with more than 10 employees: the universe of firms with more than 500 employees and a stratified sample of firms with 11-500 employees 9 . The sample is fairly representative of the Italian economic structure: 66 percent of firms have less than 50 employees, while 91 percent are below the threshold of 250 6 Consistent with the hypothesis that relational banks capture small firms, many studies concerning countries other than the USA have found that interest rates and collateral on small business loans increase with the length of the lending relationship and that the usage rates of credit lines decrease for older customers (Angelini et al 1998;Degryse and Van Cayseele 2000;Hernandez and Martinez 2006;Ono and Uesugi 2005;Barone, Felici and Pagnini 2006;Ogawa et al 2007;Grunert and Norden 2009;Jiménez et al 2009;Ioannidou and Ongena 2010). In addition, the profitability of small firms tends to be lower when they maintain exclusive relationships with few banks (Montoriol Garriga 2006).…”
Section: Datamentioning
confidence: 90%
“…A proxy for relational lending widely used in the literature is the span of time since when the firm and its main bank were tied, the basic idea being that the longer the relationship, the greater the availability of proprietary soft information and the specific resources invested by the parties in the relationship, and the more difficult it is for the bank and the firm to escape from the relationship (Petersen and Rajan 1994, Berger and Udell 1995, Degryse and Van Cayseele 2000, Ongena and Smith 2001, Elsas 2005). …”
Section: The Length Of the Bank Relationshipmentioning
confidence: 99%